2009
DOI: 10.1002/pssc.200880330
|View full text |Cite
|
Sign up to set email alerts
|

Carrier‐carrier and carrier‐phonon scattering in the low‐density and low‐temperature regime for resonantly pumped semiconductor quantum dots

Abstract: We study carrier relaxation due to Coulomb scattering and interaction with LO‐phonons in semiconductor quantum dots at low temperatures. Scattering for different relaxation process are evaluated for various carrier distributions that correspond to stages of the typical relaxation kinetics after optical excitation with a weak pulse, generating on average less than one electron per quantum dot.Even when the spacing of the quantum dot energy levels does not match the LO‐phonon energy, we.nd that carrier‐LO‐phonon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, it has been shown that the Markov approximation, leading to the emergence of the energy conserving δ-function in the scattering rates, can underestimate its actual value [SEE05,SEE09,STE12]. This is due to a broadening of the transition probabilities in energy space by non-Markovian dynamics, which makes scattering possible also for energy differences not matching the LO phonon energy exactly.…”
Section: Theory Of Quantum-dot Optical Devicesmentioning
confidence: 99%
“…However, it has been shown that the Markov approximation, leading to the emergence of the energy conserving δ-function in the scattering rates, can underestimate its actual value [SEE05,SEE09,STE12]. This is due to a broadening of the transition probabilities in energy space by non-Markovian dynamics, which makes scattering possible also for energy differences not matching the LO phonon energy exactly.…”
Section: Theory Of Quantum-dot Optical Devicesmentioning
confidence: 99%
“…However, it has been shown that the Markov approximation, leading to the emergence of the energy conserving δ-function in the scattering rates, can underestimate its actual value [42][43][44]. This is due to a broadening of the transition probabilities in energy space by non-Markovian dynamics, which makes scattering possible also for energy differences not matching the LO phonon energy exactly.…”
Section: Carrier-phonon Scatteringmentioning
confidence: 95%
“…Assuming that τ cav is small compared to all other processes determining the electric field dynamics, the above equation can be transformed to a quasi-continuous change in time: 43) where the losses have been combined to a total loss rate κ. Inserting these additional losses into Eq. (2.41), we arrive at the dynamic equation governing the time evolution of the electric field inside the cavity:…”
Section: Optical Lossesmentioning
confidence: 99%